Self-Control, Social Consequences, and Street Youths' Attitudes towards Police - Baron, Stephen W. (Canadian journal of criminology and criminal justice, 2016)
Data from a self-report survey of 400 homeless street youths are used to explore the relationship between self-control and negative orientations towards the police. The study examines whether the relationship is direct and/or mediated through its association with deviant attitudes, criminal peers, police contacts, criminal behaviour, and homelessness – factors found in past research to have been linked to young people’s attitudes towards police. Findings reveal that self-control is directly associated with negative attitudes towards the police. This relationship is mediated by deviant attitudes, criminal peers, police contacts, and criminal participation. The study shows the importance of recognizing both the direct and the indirect relationship of self-control with attitudes towards police in marginal populations as well as specifying the continued importance of various street life factors in understanding the way youth perceive the police.